The Roles of Environmental Concern, Green Perceived Value, Subjective Norms, and Green Trust Towards Green Hotel Purchase Intention - Chairunnisa, Marsya Rizqia; Perdhana, Mirwan Surya (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
With the continuous growth of the world economy, many companies believe that generating profit is vital for its sustainability. However, the profits were obtained without having consideration about any other factors such as environmental problems. At present, the earth is currently being hit by a lot of environmental problems such as global warming and climate change that was mainly caused by the human behavior with the purpose of developing their business. With that, a study of human behavior to help the earth is needed. The purpose of this study is to develop a framework to explore the influences of Environmental Concern, Green Perceived Value, Subjective Norms, And Green Trust on Green Hotel Purchase Intention. This research employs an empirical study by means of the questionnaire survey method to verify the hypotheses and to explore its managerial implications. Finally, this research offers several practical implications for developing successful businesses in Green service industry.